PRINCIPLES OF LEGAL PROTECTION OF HEALTH SERVICES FROM THE PERSPECTIVE OF SOCIO-LEGAL STUDIES - Mhd Azhali Siregar; Rahul Ardian Fikri; Ayuda Silitonga (PT. Sinergi Legal Publisher, 2024)
This study discusses the principle of legal protection in health services with a socio-legal approach. which integrates normative and sociological legal studies. The main focus of the study is on legal protection for patients and medical personnel in the context of health services in Indonesia. Optimal health services require legal certainty. especially related to the rights and obligations of all parties involved. In practice. many disputes arise due to negligence or certain medical actions. which shows a gap between normative rules and implementation in the field. The results of the study indicate that legal protection in health services does not only refer to statutory regulations such as the Health and Medical Law. but must also consider social aspects. culture. and ethics that apply in society. The socio-legal approach offers a comprehensive solution by integrating legal perspectives with social reality. so that it can create substantive justice for patients and medical personnel. From the analysis conducted. it was found that the application of a restorative justice-based approach can be an effective alternative in resolving medical disputes. in addition to formal litigation mechanisms. This is because this approach is more capable of fulfilling a sense of justice for victims. perpetrators. and the wider community. This study concludes that strengthening regulations and implementing legal principles in health services. by considering social aspects. is an important step to achieving a fair. effective. and sustainable health system